Advancing Supercapacitors with Coconut Rachis Activated Carbon: A Sustainable Electrode Material - Bindhu Devu; Sreekala Chandrasekharan Omanaamma; Misnon Izan Izwan; Jose Rajan (E3S Web of Conferences)
Carbon derived from renewable energy sources plays a crucial role in fostering sustainability within supercapacitor applications. This study investigates the use of activated carbon produced from a unique biomass source, coconut rachis, containing approximately 81% carbon, as a potential electrode material. The coconut rachis-derived activated carbon features a high surface area (around 1630 m2·g−1) and a honeycomb-like surface structure, which enhance its ability to adsorb electrolyte ions efficiently. This carbon is termed as honeycomb-shaped porous carbon (HSPC). The performances of these electrodes in adsorbing different cations, i.e., Na+ and Li + in 1M Na2SO4 and 1M Li2SO4 electrolytes, were studied and reported a higher specific capacitance. The supercapacitor performance using 1M Na2SO4 as an electrolyte shows a high energy density and potential window. The supercapacitor also shows excellent cyclic stability with an increment in capacitance retention from 82 % to 93% over 2000 cycles. Keywords: Renewable carbon, Bioresources, Electrochemical Double Layer Capacitor (EDLC), Cation adsorption, Supercapacitors.